Effect of Ni content and Al2O3 particle size on the thermal and mechanical properties of Al2O3/Ni composites prepared by spark plasma sintering. (November 2018) - Irshad, Hafiz Muzammil; Hakeem, Abbas Saeed; Ahmed, Bilal Anjum; Ali, Sharafat; Ali, Sadaqat; Ali, Sameer; Ehsan, Muhammad Ali; Laoui, Tahar
Abstract: Alumina-nickel composites were prepared by carrying out spark plasma sintering (SPS) of nano-sized and micro-sized Al2 O3 particles with 15–45 wt% Ni powders. The powder materials were sintered at a temperature of 1400 °C under a constant uniaxial pressure of 50 MPa. FESEM micrographs of the products showed uniformly dispersed nickel inclusions in both matrices at intergranular positions. Presence of Al2 O3 as the major phase along with Ni as the minor phase was confirmed using XRD analysis. Thermal and mechanical properties of the nano- and micro-sized Al2 O3 /Ni composites were investigated. The thermal conductivity of nano-sized alumina composites was seen to increase with the increase in nickel content, however, an opposite trend was observed for micro-sized alumina-based composites. Moreover, thermal conductivities of all the composites decreased with increase in temperature. The composites also showed high hardness and fracture toughness values of up to 19.6 GPa and 4.71 MPa ∗ m 1/2, respectively, and relative density values, between 79 and 99%, that decreased with increasing Ni content. Furthermore, the nano-sized Al2 O3 /Ni composites showed thermal and mechanical properties superior to those of the micro-sized Al2 O3 /Ni composites. Graphical abstract: Unlabelled Image Highlights: Nano- and micro-sized alumina composites containing 15–45 wt% of nickel (Ni) are densified by spark plasma sintering (SPS). Effects of Ni content and alumina powder size were systematically investigated. Nano-alumina/Ni composites have high values of hardness up to 20 GPa. The addition of Ni in nano-sized alumina/Ni composites increases the fracture toughness and thermal properties. Nano-sized alumina/Ni composites have superior thermal and mechanical properties as compared to micro-sized alumina/Ni composites.